1996
DOI: 10.1037/0735-7028.27.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Mental health consultation in the pediatric intensive care unit.

Abstract: The need for psychosocial intervention to be integrated with medical care on intensive care units is high, but too often mental health professionals are ill-equipped by traditional training programs for such work. Medical crisis counseling provides a conceptual framework useful in developing the skills needed to effectively intervene in such settings. The pediatric intensive care unit (PICU) is arguably one of the most emotionally demanding and high-stress areas where mental health clinicians may be asked to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…18 Previous work has also documented the pivotal and often intense role that critical care staff can play in supporting some families at the end of life. 18,42,45,47,48 Staff members' genuine expression of emotions and concern is generally perceived positively, encouraged, and well-remembered by parents. 18,49 Indeed, clinicians need not fear displaying their empathy and own emotions, for this is the very substance that can convey one's humanity and matters deeply to parents.…”
Section: Emotional Expression and Support Of Staffmentioning
confidence: 97%
See 1 more Smart Citation
“…18 Previous work has also documented the pivotal and often intense role that critical care staff can play in supporting some families at the end of life. 18,42,45,47,48 Staff members' genuine expression of emotions and concern is generally perceived positively, encouraged, and well-remembered by parents. 18,49 Indeed, clinicians need not fear displaying their empathy and own emotions, for this is the very substance that can convey one's humanity and matters deeply to parents.…”
Section: Emotional Expression and Support Of Staffmentioning
confidence: 97%
“…40,41 Unfortunately, the prevailing mode of end-of-life discussions focusing on laboratory values, organ systems, and individual treatments may be too specific and disjointed to facilitate understanding and decision-making or to meet the family's psychosocial needs. 10,18 End-of-life discussions that focus on organ systems or offer information only on a need-to-know basis may not hit the mark 18,39,42 and can leave some families feeling overwhelmed, underinformed, or wondering what the information means relative to their child's quality of life and survival.…”
Section: Information Access Communication and Coordinationmentioning
confidence: 97%
“…A body of work has identified that nurses as a professional group are subject to high levels of emotional intensity and stress and are often in intimate contact with death, illness, and trauma, considered above that which an ordinary person could bear (Lawrence, 1995; Menzies‐Lyth, 1988; Meyer, DeMaso, & Koocher, 1996). Meyer et al.…”
Section: Adolescence Professional Defense and Trauma: A Psychodynammentioning
confidence: 99%
“…A body of work has identified that nurses as a professional group are subject to high levels of emotional intensity and stress and are often in intimate contact with death, illness, and trauma, considered above that which an ordinary person could bear (Lawrence, 1995; Menzies‐Lyth, 1988; Meyer, DeMaso, & Koocher, 1996). Meyer et al. suggests that the stress experienced by pediatric nurses may be even more intense because of the level of variability in the kinds of patients they work with and the societal expectations that exist for children's health and lifespan.…”
Section: Adolescence Professional Defense and Trauma: A Psychodynammentioning
confidence: 99%
“…In addition, the past two decades have seen psychology merge with other health/wellness disciplines-especially in the area of medicine. For example, opportunities now are available for psychologists in the areas of behavioral medicine, cardiology, pediatrics, neurology, surgery, oncology, spinal cord injury units, and genetic counseling (Allan & Sheidt, 1996;Asken, 1979;Blanchard, 1982;Carpenter, 1989;Cummings, 1992;Dana & May, 1986;Drotar, 1998;Gabinet & Friedson, 1980;Masur, 1979;Meyer, DeMaso, & Koocher, 1996;Sayette & Mayne, 1990;Shiloh, 1996;Taylor, 1987;Tovian, 1991).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%